Suburbanisierung und Suburbia im kontinentalen Europa – eine Standortbestimmung - Hesse, Markus; Siedentop, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
This paper provides a brief overview of recent developments and debates concerned with suburbanisation in continental Europe. While current discourses in urban research and practice still focus on processes of reurbanisation and the gentrification of inner-city areas, suburbia continues to exist and thrive. Depending on the definition applied, suburban areas still attract a large share of in-migration and employment growth in cities of the developed countries. Given that popular meta-narratives on suburbia and suburbanisation are often spurred by, or refer to, North American suburban studies, we take a different perspective here, one based on continental European trajectories of development in and across city-regional areas that are considered to be suburban, and on social processes that are associated with suburbanisation (suburbanisms). Thus, we aim to avoid a biased understanding of suburbia as a spatial category, which is often considered mono-functional, non-sustainable, or in generic decline. Instead, we observe that suburban variety is huge, and the distinction between urban core and fringe seems to be as ambiguous as ever. The paper, which also introduces the theme of this special issue of “Raumforschung und Raumordnung | Spatial Research and Planning”, bundles our findings along four themes: on suburbia as a place of economic development, on the shifting dynamics of housing between core and fringe locales, on the life-cyclic nature of suburbanisation, and on strategies for redevelopment. Finally, we discuss certain topics that may deserve to be addressed by future research, particularly on the European variant of suburbanisation and suburbs.
Keywords: Suburbanisation; Suburbs; City regions; Europe